Aerobic exercise and gut flora: a key link to improved cognitive impairment in mice with Parkinson’s disease - Shan, Wen Peng; Yan, Shi Lei; Guo, Yuan Yuan; Yang, Hua Ke; Wang, Jing Chun; Xiang, Jie (Frontiers in Aging Neuroscience, 2025)
BackgroundParkinson’s disease (PD) is a common neurodegenerative disorder. It is marked by motor dysfunction and cognitive decline. In recent years, scientific studies have found that PD’s pathogenesis may be tied to an imbalance in the gut microbiota. This offers new perspectives for PD treatment. Modulating the gut microbiota is recognized as a potential way to enhance PD symptoms. While aerobic exercise can positively influence the gut microbiota, research on how the gut microbiota mediates aerobic exercise’s effects on PD cognitive impairment is still limited. Thus, this study aimed to explore the potential mechanisms by which aerobic exercise improves cognitive impairment in PD patients. It does so by modulating the gut microbiota’s structure and, in turn, improving cognitive function. Through this study, we hope to offer new strategies and a theoretical basis for treating PD cognitive impairment.MethodsThis study focused on the potential neuroprotective effects of long-term aerobic exercise in an MPTP-induced PD mouse model. Research methods included using 16S rRNA gene sequencing and plasma untargeted metabolomics to precisely describe the composition of the mouse gut microbiota and its metabolite changes. We also monitored the mice’s motor and cognitive functions via behavioral assessments. Pathological features and molecular-level changes in PD mice were analyzed using morphological and molecular biology techniques. To further study the role of gut microbes in aerobic exercise, we conducted antibiotic treatment experiments on mice. Finally, Pearson correlation analysis was used to explore the correlation between gut microbiota, plasma metabolite outcomes, and molecules related to cognitive function.ResultsOur results showed that aerobic exercise effectively intervened in PD mice. It alleviated PD-related pathological impairments and cognitive deficits and promoted the secretion of FNDC5 and BDNF, producing neuroprotective effects. Aerobic exercise regulated the gut flora imbalance in PD mice. 16S rRNA analysis revealed a significant increase in the abundance of Alloprevotella, Akkermansia, Lachnospiraceae_NK4A136_group, Bacteroides, and Prevotellaceae_UCG-001. In contrast, the abundance of Parabacteroides, Helicobacter, Alistipes, and Odaribacter decreased significantly. The gut flora mediated the role of aerobic exercise by regulating FNDC5 secretion through PGC1-α/CREB and influencing BDNF production.ConclusionAerobic exercise improves gut flora imbalance in PD mice. It also attenuates PD-related pathological impairments and cognitive deficits. However, its efficacy on non-motor symptoms can be nullified by antibiotics. The gut flora-mediated aerobic exercise exerts neuroprotective effects on PD by regulating FNDC5 secretion via PGC1-α/CREB.